Zero Curriculum Communication Strategy in Implementing the Merdeka Curriculum - hidayatulloh, Syarif; Larasaty, Past Novel (Akademika, 2025)
This study examines the communication tactics employed by Telesandi Bekasi Telecommunication Vocational School in the execution of the independent curriculum. The adoption of the autonomous curriculum is neither obligatory nor optional, resulting in disparities over its application for new students at Telesandi Bekasi Telecommunication Vocational School. Due to variations in the implementation of curriculum backgrounds from Junior High Schools (SMP), incoming pupils entering the ninth grade will possess disparate experiences with the curriculum. Consequently, Telesandi Bekasi Telecommunications Vocational School must identify the communication tactics for the implementation of the independent curriculum for incoming students. Telesandi Bekasi Telecommunication Vocational School employs a communication approach centered around the establishment of a Zero Curriculum. The objective is for all new students entering class X to possess uniform proficiency levels, despite their varied experiences in utilizing the curriculum throughout junior high school (SMP). The implementation of the Zero Curriculum results from innovation derived from the theory proposed by Everett M. Rogers in his work, Diffusion of Innovations. This Zero Curriculum will positively influence new students in their subsequent engagement with the independent curriculum. This essay aims to enable readers to utilize the zero curriculum as a strategic measure in the implementation of the autonomous curriculum inside their schools.